TURKISH COMMUNITY’S VACCINE HESITANCY: A COMMUNITY-BASED RESEARCH - Melek Yağci Özen; Yuceler, Aydan; Alabed, Alabed Ali Ahmed (Malaysian Journal of Public Health Medicine, 2023)
Vaccination, which has played an active role in reducing or eliminating epidemics in the historical process, has been met with resistance by some individuals for various reasons. This resistance includes different forms of behavior called anti-vaccine, ranging from being against some vaccines to rejecting all vaccines. In this study, it was aimed to examine the change in the level of anti-vaccination, which tends to increase worldwide during the covid-19 period, depending on socio-demographic variables. In the study, it was questioned whether there was a significant difference between the socio-demographic characteristics of the participants, their covid-19, experiences, and the scores they got from the Anti-Vaccination Scale. At the end of the analysis, it was observed that there was no significant difference between the total score of the anti-vaccine scale and the anti-vaccination levels according to the gender, marital status, presence of chronic disease, and covid-19 experiences of the participants. On the other hand, it was observed that there were differences in the levels of anti-vaccination depending on age, education level, income status, and several children. It is among the results of the research that the level of opposition to vaccination is high among younger individuals, with lower educational levels and income levels, and hesitations towards vaccination are justified due to the increase in the number of children.